Identity Formation among North Korean Defectors in South Korea: Implications from a Socio-Cultural Learning Theoretical Lens - Hyewon Park; Junghwan Kim (Adult Education Research Conference, 2014)
This paper aims to analyze the present situation of North Korean Defectors (NKDs)’ adaptation in South Korea from the relationship between social adjustment and identity construction. By using a socio-cultural learning theoretical lens, it reveals structural barriers and tacit differentiations to hinder NKDs’ participation and to disturb their identity formation.